Penerapan Permainan Kecil terhadap Motivasi Belajar Siswa dalam Pembelajaran PJOK pada Siswa Kelas X SMK Negeri 1 Kediri - Suci Elmasari; Dony Andrijanto (Departement of Mathematics Education, 2024)
Small games generally do not have standard rules, such as game rules, type of equipment, area size, and length of playing time. The provision of games is adjusted to the situations and conditions that occur when carrying out the activity. Motivation is the main key in learning. When students are motivated, they tend to be more enthusiastic and actively participate in learning so they are able to achieve learning goals. The objectives of this research are to determine the effect of implementing small games on student learning motivation in learning PJOK in class X students at SMK Negeri 1 Kediri and determine the magnitude of the influence of implementing small games on student learning motivation in learning PJOK in class X students at SMK Negeri 1 Kediri. This research is pure experimental research with a quantitative approach. The design used is Randomized Control Group Pre-test Post-test Design. The population in this study were class X students at SMK Negeri 1 Kediri with a sample selection of 63 students using the purposive sampling method. Based on the results of data analysis, it is known that there is an influence of implementing small games on student learning motivation in learning PJOK in class X students at SMK Negeri 1 Kediri. This is proven by the results of the Wilcoxon signed rank test in the experimental class with a sig value. amounting to 0.002 < 0.05 with a percentage increase of 10.5%.